2022
DOI: 10.3389/fimmu.2022.997853
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of RDW for the prediction of mortality in adult sepsis patients: A systematic review and meta-analysis

Abstract: BackgroundRed blood cell distribution width (RDW) is a common biomarker of bacterial infections, and it can be easily obtained from a routine blood test. We investigate the diagnostic value of RDW for the prediction of mortality in adult sepsis patients through a review and meta-analysis. We registered this review in PROSPERO (Registration Number: CRD42022357712), and the details of the registration are included in Appendix 1.MethodsWe searched PubMed, Cochrane Library, Springer, and Embase between Jan. 1, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Previous studies have also reported a close association between early elevation of WBC and adverse prognosis, suggesting that WBC may serve as a prognostic factor, as confirmed by the present study [ 5 , 10 , 17 ]. The RDW has recently been found to have a strong predictive capacity for the risk of death and adverse outcomes of other infectious and serious diseases, such as COVID-19 [ 18 ], acute respiratory obstruction syndrome [ 19 ], and sepsis [ 20 ]. Studies of ICU patients have shown that the RDW is an independent risk factor for death and is significantly and independently related to mortality [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported a close association between early elevation of WBC and adverse prognosis, suggesting that WBC may serve as a prognostic factor, as confirmed by the present study [ 5 , 10 , 17 ]. The RDW has recently been found to have a strong predictive capacity for the risk of death and adverse outcomes of other infectious and serious diseases, such as COVID-19 [ 18 ], acute respiratory obstruction syndrome [ 19 ], and sepsis [ 20 ]. Studies of ICU patients have shown that the RDW is an independent risk factor for death and is significantly and independently related to mortality [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond merely serving as a prognostic marker for mortality in conditions such as heart disease, kidney disease, and cancer, the significance of RDW extends further. It encompasses the assessment of inflammation levels in conditions like sepsis and autoimmune diseases and the evaluation of infection severity, and it may also offer insights into the presence of neurological or liver disorders [ 15 , 17 , 19 , 20 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“… 36 RDW, whether used alone or in combination with other clinical and laboratory parameters, has demonstrated prognostic value in predicting clinical outcomes in sepsis. 37 However, there are limited studies utilizing the coefficient of variation (RDW-CV) of RDW to predict clinical outcomes in sepsis. On the other hand, sepsis often leads to significant coagulation dysfunction.…”
Section: Discussionmentioning
confidence: 99%